2021
DOI: 10.1038/s41467-021-22913-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein analysis of extracellular vesicles to monitor and predict therapeutic response in metastatic breast cancer

Abstract: Molecular profiling of circulating extracellular vesicles (EVs) provides a promising noninvasive means to diagnose, monitor, and predict the course of metastatic breast cancer (MBC). However, the analysis of EV protein markers has been confounded by the presence of soluble protein counterparts in peripheral blood. Here we use a rapid, sensitive, and low-cost thermophoretic aptasensor (TAS) to profile cancer-associated protein profiles of plasma EVs without the interference of soluble proteins. We show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(160 citation statements)
references
References 60 publications
(29 reference statements)
1
158
1
Order By: Relevance
“…D Acoustic-based isolation / Thermophoretic enrichment. Copyright 2021 by Tayebi [ 67 ], 2019 by Liu [ 68 ], 2021 by Tian [ 69 ] …”
Section: New Enrichment Methodsmentioning
confidence: 99%
“…D Acoustic-based isolation / Thermophoretic enrichment. Copyright 2021 by Tayebi [ 67 ], 2019 by Liu [ 68 ], 2021 by Tian [ 69 ] …”
Section: New Enrichment Methodsmentioning
confidence: 99%
“…EV cargo consists of a number of bioactive molecules, including nucleic acids, lipids and membrane-bound and cytosolic proteins. The uptake of EVs is able to influence cell behaviour and as such, EVs are known to be important signalling particles, as well as diagnostic, predictive and prognostic biomarkers in diseases [ 39 ]. Although EVs can be categorised in a number of ways (e.g., based on size, cargo and biological role), they are most often classified based on their biogenesis, with exosomes and microvesicles being the most commonly discussed EV subtypes ( Figure 2 ).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…This prospective cohort verified that a higher value of EV signature was significantly associated with an inferior PFS in Kaplan–Meier analysis (log-rank test: p = 0.033 for the EV). Collectively, these results imply that the EV signature may serve as an independent marker for metastatic BC prognosis [ 39 ].…”
Section: Clinical Applications Of Extracellular Vesicles In Therapy Resistancementioning
confidence: 99%
“…The author suggested that analyzing individual EVs can provide more precise information for cancer diagnosis and that using a combination of proteins can improve the detection sensitivity (28). Then, Tian et al (46) found that the weighted sum of eight plasma EV protein markers [including mucin-1, CA-125, carcinoembryonic antigen, HER2, EGFR, prostate-specific membrane antigen (PSMA), EpCAM, and vascular endothelial growth factor (VEGF)] was able to distinguish among metastatic BC, nonmetastatic BC, and healthy donors with an overall accuracy of 91.1%. In addition, the aptasensor method used in this study has advantages in that preseparation of EVs is not needed, the total detection time is short (within 3 h), and it has a low cost (less than $1).…”
Section: Candidate Ev Proteins For Bc Diagnosismentioning
confidence: 99%